2010
DOI: 10.1253/circj.cj-09-0772
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Landiolol, an Ultra-Short-Acting .BETA.1-Selective Blocker, on Electrical Storm Refractory to Class III Antiarrhythmic Drugs

Abstract: Background:Occasionally it is difficult to inhibit electrical storm (ES) with standard pharmacological treatment. In the present study the effect of landiolol, an ultra-short-acting β1-selective blocker, on ES refractory to class III antiarrhythmic drugs was evaluated. Methods and Results:The study group comprised 42 consecutive patients who developed ES for which intravenous class III antiarrhythmic drugs, such as amiodarone and nifekalant, were ineffective. Landiolol was administered intravenously with an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 22 publications
0
34
0
1
Order By: Relevance
“…Many studies have shown that antiarrhythmic drug and β-blocker therapies at the acute phase of MI affect prognosis in patients with MI. 24 Similarly, we do not know the effect of these drugs in this study.…”
Section: Study Limitationsmentioning
confidence: 75%
“…Many studies have shown that antiarrhythmic drug and β-blocker therapies at the acute phase of MI affect prognosis in patients with MI. 24 Similarly, we do not know the effect of these drugs in this study.…”
Section: Study Limitationsmentioning
confidence: 75%
“…In the setting of cardiac arrest, the patient not only has a swell of endogenous catecholamines, but is also receiving exogenous epinephrine every 3–5 minutes 6. Several studies report on survival with positive neurological outcome through the use of standard class III antiarrhythmics with subsequent administration of short-acting beta blockers 67, 1112…”
Section: Discussionmentioning
confidence: 99%
“…11 Based on these properties, landiolol has been reported to be useful for treating several acute disorders, including arrhythmias during heart surgery, 12 acute myocardial infarction, 13 acute decompensated heart failure, 14 and refractory electrical storm. 15 Ultra-short-acting β-blockers may be useful to control the HR with minimal effects on cardiac function because the negative inotropic effect is not sustained after decreasing the dose or stopping administration of these drugs. Therefore, the present study was designed to evaluate the efficacy and safety of intravenous landiolol for achieving rapid control of tachycardia in patients with AF/AFL and LV dysfunction.…”
Section: Editorial P 893mentioning
confidence: 99%